2009
DOI: 10.1007/s11250-009-9344-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of replacing Dichantium hay with banana (Musa paradisiaca) leaves and pseudo-stem on carcass traits of Ovin Martinik sheep

Abstract: A study was done to evaluate banana (Musa paradisiaca) as a forage (leaves and pseudo-stems) for feeding Ovin Martinik lambs (OMK), with the aim to test its impact on carcass quality. Forty four intact OMK male were used after weaning with an initial mean live weight of 14.4 (+/- 3.3) kg, reared in individual pens. Animals were offered either Dichantium hay (control diet, Dh) or cut chopped leaves and pseudo-stems of banana (experimental diet, Blps). They were fed 200-250 g x d(-1) of commercial concentrate. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Direct substitution of banana leaves and pseudostem (Musa paradisiaca) as forage in the diet of Ovin Martinik sheep shows no significant difference in carcasses quality compared to sheep feeding on normal hay forage diet (Marie-Magdeleine et al 2009). The sheep carcass did not differ in terms of overall weight and chemical composition of the meat.…”
Section: Animal Feedsmentioning
confidence: 98%
“…Direct substitution of banana leaves and pseudostem (Musa paradisiaca) as forage in the diet of Ovin Martinik sheep shows no significant difference in carcasses quality compared to sheep feeding on normal hay forage diet (Marie-Magdeleine et al 2009). The sheep carcass did not differ in terms of overall weight and chemical composition of the meat.…”
Section: Animal Feedsmentioning
confidence: 98%
“…The leaves and pseudostem of banana trees are residues from culturing or fruit harvesting practices, and may be viable byproducts for use in lamb feeding (ARCHIMÈDE et al, 2012;MARIE-MAGDELEINE et al, 2009), especially in the semi-arid regions of Brazil, due to the availability and nutritional characteristics of these products. Ribeiro et al (2007) found high crude protein content (17.20%) in banana leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Means slaughter weight (24. 3 ± 1.0 kg) was gained in 58 days, reach in both cases in less time than the results described by Marie-Magdeleine et al (2009) which Ovin Martinik sheep, where lambs spend 90 days to reach 22-24 kg feeding also with banana by-products. 26.7 ± 9.45 28.9 ±7.49 NS NS: Non statistical significant P < 0.05 pH0: pH at the time of slaughter; pH1: pH 24 h after slaughter; L0: lightness at the time of slaughter; Chroma 0:at the time of slaughter; Hue0:at the time of slaughter; L1: lightness 24 h after slaughter; Chroma1: after 24 of slaughter; Hue1: after 24 h after slaughter…”
Section: Discussionmentioning
confidence: 50%
“…Different parts of the fruit (peels) and the plant (leaves, stems, and stalks or pseudostems) are used in animal feeding as fresh plantain, ensiled and can be dehydrated, chopped, milled or cooked, to fed to livestock (Ecocrop 2010;Heuzé and Tran 2016). Dried banana leaves and pseudo stems have been used to feed goats and sheep by (González-García et al 2008;Marie-Magdeleine et al 2009;Heuzé and Tran 2016;Barbera et al 2018) achieving good results on intake and growth performance. Hence, the evidence of its nutritional value has been demonstrated in pigs and ruminants.…”
Section: Introductionmentioning
confidence: 99%